Analysis of Energy Consumption and Carbon Emissions in Traditional versus Smart Manufacturing Practices: A Case Study in the Steel Industry - Mohit Beniwal; Dr. Lalit Narayan (International Journal of Scientific Research in Science and Technology, 2025)
This study investigates the disparities in energy consumption and carbon emissions between traditional manufacturing processes and smart manufacturing practices in the steel industry. Utilizing a comparative analysis approach, the research employs quantitative methods, including descriptive and inferential statistics, to scrutinize differences in energy usage and emissions levels. Data collected from a stratified sample of manufacturing facilities are analyzed using independent samples t-tests and effect size calculations. Ethical considerations guide the research methodology, ensuring compliance with privacy protection and informed consent. The findings reveal that while there are observable variations in energy consumption and carbon emissions between the two manufacturing paradigms, these differences are not statistically significant. The study contributes to the understanding of sustainability challenges in manufacturing and informs evidence-based decision-making for industry stakeholders and policymakers.
Keywords: Energy consumption; carbon emissions; smart manufacturing; traditional manufacturing; steel industry; comparative analysis; statistical tests; sustainability